2020
DOI: 10.1097/sla.0000000000003831
|View full text |Cite
|
Sign up to set email alerts
|

Heavyweight Mesh Is Superior to Lightweight Mesh in Laparo-endoscopic Inguinal Hernia Repair

Abstract: Objective: This meta-analysis and trial sequential analysis aims to provide an update on the available randomized controlled trials (RCTs) and recommendations on using lightweight mesh (LWM) or heavyweight mesh (HWM) in laparo-endoscopic inguinal hernia repair. Background: LWM might reduce chronic pain through improved mesh flexibility and less fibrosis formation. However, in laparo-endoscopic repair chronic pain is already rare and LWM raise concerns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Perhaps more relevant is the collective experience of clinical trials that compare mesh weights for laparoscopic inguinal hernia repair because this mesh is similarly placed in the retromuscular position. Although lightweight mesh has demonstrated limitations in regard to durability for such repairs, these trials have likewise found no difference between rates of pain and foreign-body sensation. Finally, 2 randomized clinical trials comparing mesh weight in open ventral hernia repair likewise found no patient-perceived benefits to the lightweight material.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more relevant is the collective experience of clinical trials that compare mesh weights for laparoscopic inguinal hernia repair because this mesh is similarly placed in the retromuscular position. Although lightweight mesh has demonstrated limitations in regard to durability for such repairs, these trials have likewise found no difference between rates of pain and foreign-body sensation. Finally, 2 randomized clinical trials comparing mesh weight in open ventral hernia repair likewise found no patient-perceived benefits to the lightweight material.…”
Section: Discussionmentioning
confidence: 99%
“…The authors affirmed that the peritoneal incision and closure with continuous suture may be responsible for high pain scores for TAPP repair. However, not only the peritoneal incision is determinant of postoperative pain, but also several factors including patients' subjective pain perception and expression, different protocols for anesthesia, postoperative analgesia, methods for mesh fixation (tacks vs. glue vs. self-gripping), mesh type, and weight (g/m 2 ) have been shown to be additional causes of postoperative pain [56][57][58][59]. While our results seem to support equivalent Surgeon experience, expertise, variation in technical skills, and hospital volume are key determinants for operative time while TAPP and TEP have been shown to be associated with a steep learning curve [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…A trend is slowly emerging in the literature to use heavier implants in the case of large and complex inguinal defects treated with laparoendoscopic techniques. Some studies point to the superiority of heavier implants in the context of recurrence, especially when routine xation is not used (14,15).…”
Section: Discussionmentioning
confidence: 99%